PERBANDINGAN EFEK EKSTRAK BUAH ALPUKAT (Persea americana Mill) TERHADAP PERTUMBUHAN BAKTERI Pseudomonas aeruginosa DENGAN METODE DISK DAN SUMURAN - Sri Dewi Haryati; Sri Darmawati; Wildiani Wilson (Universitas Muhammadiyah Semarang, 2017)
This study aimed to analyze the concentration of avocado fruit extracts method disc and wells 10% b/v, 20% b/v, 30% b/v, 40% b/v and 50% b/v in inhibited P.aeruginosasa. The avocado fruit is extracted using the maceration method. Then the activity of avocado fruit to the growth of P.aeruginosa using the method of disc and wells.The results showed the extract of avocado method of disk and wells at concentration10% b/v, 20% b/v, 30% b/v, 40% b/v and 50% b/v can inhibit P.aeruginosa bacteria the mean inhibitory zone of the disc method was 16.6 mm, 21.6 mm, 26.0 mm, 28.4 mm and 29.6 mm, as well as in the method of wells obtained mean inhibition zone respectively that is 25.4 mm, 27.4 mm, 28.8 mm, 30.2 mm and 31.2 mm.The positive control used was ciprofloxacin concentration of 25 μg forming a 33 mm inhibitory zone diameter. One Way ANOVA test was obtained p=0,000 which shows that there is an average difference between the inhibitory zone diameter between concentrations 10% b/v, 20% b/v, 30% b/v, 40% b/v and 50% b/v, as well as there is a marked difference between the disk method and the extraction of avocado extract on the growth of P.aeruginosa.The result shows that the average of the bacterial inhibition zone with the disk method is lower than the well method, the higher the concentration of avocado extract, the higher the inhibitory effect on the growth of P.aeruginosa bacteria. Keywords: Avocado Fruit Extracts, P.aeruginosa, Method Disc, Methode Wells